KINERJA PERUSAHAAN PENGARUH DARI STRUKTUR MODAL, PROFITABILITAS DAN UKURAN PERUSAHAAN - Dede Hertina; Mohamad Bayu Herdiawan Hidayat; Fika Deningtyas (Universitas Nusa Cendana, 2021)
This study aims to determine the effect of Capital Structure, Profitability, Company Size on the Performance of the cigarette sub-sector companies listed on the IDX in 2014-2018. This research uses descriptive and verification methods with regression analysis tools and the coefficient of determination. The results of data processing analysis of the coefficient of determination obtained a fairly strong and unidirectional closeness of the relationship between the independent variable and the dependent variable and has a determination coefficient value of 47.91%. The results of testing the F test hypothesis indicate that the Capital Structure, Profitability and Company Size simultaneously have a significant effect on company Performance. Hypothesis testing using t test shows that Capital Structure has no significant effect on company Performance. Profitability has a significant effect on company Performance and Company Size has a significant effect on company Performance. Keywords: Capital Structure, Profitability, Company Size, Company Performance